PERAN CUSTOMER TRUST MEMEDIASI PENGARUH CUSTOMER EXPERIENCE TERHADAP POSITIVE WORD OF MOUTH (Studi Pada Konsumen Cat Café Sanur) - Hapsari, Kadek Sita Artha; Warmika, I Gede Ketut (E-Jurnal Manajemen, 2021)
A pleasant experience is important in running a business in order to improve company performance. This study explain the role of customer trust in mediating the effect of customer experience on positive word of mouth. The sample in this study used a purposive sampling method, taking 104 samples, respondents who had visited Cat Café Sanur with the criteria of being domiciled in Bali, an Indonesian citizen, had visited Cat Café Sanur at least once, the last education was SMA / SMK equivalent. The research data was collected by distributing questionnaires with the data analysis technique is path analysis. Based on the results of data analysis, it was found that the customer experience variable had a significant and positive effect on customer trust and positive word of mouth; customer trust has a significant and positive effect on positive word of mouth; customer trust significantly and positive mediates the effect of customer trust on positive word of mouth. Keywords: Customer experience, customer trust, positive word of mouth